Basis and Principles of Systematic Thinking in Education - Mardianto Mardianto; Saiful Ahyar; Zainal Abidin (Edumaspul: Jurnal Pendidikan, 2022)
This research is a literature study that examines the basic principles and principles of systematic thinking in education. background of the need for systematic thinking in the world of education, the results of the study show that in systems thinking, this structure (a set of causal circles) determines the behavior (behavior or dynamics) of a phenomenon. A positive causal circle will result in a growth or decline behavior. Positive causal loops are also known as Reinforcing loop types or use the "R" notation. Meanwhile, a negative causal circle will result in a goal-seeking behavior, although sometimes the goals or objectives in the circle are not seen explicitly. The negative causal circle is also a balancing process using the notation "B".